A broadband seismological observatory at Larsemann Hills, Antarctica: Noise characteristics and data quality - B Padma Rao; Jha Krishna; Thatikonda Suresh Kumar (Polar Science, 2023)
Antarctica, the southernmost ice-covered continent, plays a pivotal role in unraveling Earth's intricate evolutionary processes. Several studies have been conducted to comprehend the crustal structure of West Antarctica. However, our understanding of the sub-surface structure in the East Antarctica region, particularly along Princess Elizabeth Land (PEL), remains limited due to the scarcity of geophysical data. To bridge this knowledge gap, we (NCESS) established a permanent broadband seismological observatory in the captivating region of Larsemann Hills, East Antarctica. In addition, we investigate the noise characteristics at the station, employing power spectral density (PSD) measurements. Results have been promising, indicating that the noise levels are within the range of New High Noise Model and New Low Noise Model. Monthly variations in PSD reveal different noise levels throughout the year, with winter months exhibiting lower levels of microseismic noise attributed to lower temperatures and frozen sea surfaces. The long-period noise is higher in April & May, possibly due to high-speed winds and lower in September & October. The outcomes serve as a testament to the success of our installation and ensure a valuable data set. The data will contribute to a comprehensive investigation of sub-surface structures in the PEL region of East Antarctica, enhancing our understanding of geological processes and tectonic evolution. Furthermore, the findings will serve as a valuable resource for future research and contribute to our knowledge of Earth's dynamic processes. journal article